Bortezomib induces canonical nuclear factor-κB activation in multiple myeloma cells - Hideshima, Teru (American Society of Hematology, 2009)
Bortezomib is a proteasome inhibitor with remarkable preclinical and clinical antitumor activity in multiple myeloma (MM) patients. The initial rationale for its use in MM was inhibition of nuclear factor (NF)-κB activity by blocking proteasomal degradation of inhibitor of κBα (IκBα). Bortezomib inhibits inducible NF-κB activity; however, its impact on constitutive NF-κB activity in MM cells has not yet been defined. In this study, we demonstrate that bortezomib significantly down-regulated IκBα expression and triggered NF-κB activation in MM cell lines and primary tumor cells from MM patients. Importantly, no inhibition of p65 (RelA) nuclear translocation was recognized after bortezomib treatment in a murine xenograft model bearing human MM cells. Bortezomib-induced NF-κB activation was mediated via the canonical pathway. Moreover, other classes of proteasome inhibitors also induced IκBα down-regulation associated with NF-κB activation. Molecular mechanisms whereby bortezomib induced IκBα down-regulation were further examined. Bortezomib triggered phosphorylation of IκB kinase (IKKβ) and its upstream receptor-interacting protein 2, whereas IKKβ inhibitor MLN120B blocked bortezomib-induced IκBα down-regulation and NF-κB activation, indicating receptor-interacting protein 2/IKKβ signaling plays crucial role in bortezomib-induced NF-κB activation. Moreover, IKKβ inhibitors enhanced bortezomib-induced cytotoxicity. Our studies therefore suggest that bortezomib-induced cytotoxicity cannot be fully attributed to inhibition of canonical NF-κB activity in MM cells.